Identification of Apigenin and Luteolin in Artemisia annua L. for the Quality Control - Phadungrakwittaya, Rattana; Chotewuttakorn, Sirikul; Piwtong, Panachai; Thamsermsang, Onusa; Laohapand, Tawee; Akarasereenont, Pravit (Siriraj Medical Journal, 2019)
Objective: To identify active compounds and establish the chemical fingerprint of Artemisia annua L. for the quality control. Methods: Thin-layer chromatography (TLC) conditions were developed to screen for 2 common flavonoids (apigenin and luteolin). Three mobile phases were used to isolate these flavonoids in 80% ethanolic extract of A. annua. Hexane : ethyl acetate : acetic acid (31:14:5, v/v) and toluene : 1,4-dioxane : acetic acid (90:25:4, v/v) were used in normal phase TLC (NP-TLC), and 5.5% formic acid in water : methanol (50:50, v/v) were used in reverse phase TLC (RP-TLC). Chromatograms were visualized under visible light after spraying with Fast Blue B Salt. Apigenin and luteolin bands were checked by comparing their Rf values and UV-Vis absorption spectra with reference markers. Results: Apigenin and luteolin were simultaneously detected with good specificity in RP-TLC condition, while only apigenin was detected in NP-TLC condition. Apigenin band intensity was higher than luteolin band intensity in both conditions. Conclusion: This knowledge can be applied to the development of quality control assessments to ensure product efficacy and consistency.